Cardiac Structure and Function Across the Glycemic Spectrum in Elderly Men and Women Free of Prevalent Heart Disease. (May 2015) - Skali, Hicham; Shah, Amil; Gupta, Deepak K.; Cheng, Susan; Claggett, Brian; Liu, Jiankang; Bello, Natalie; Aguilar, David; Vardeny, Orly; Matsushita, Kunihiro; Selvin, Elizabeth; Solomon, Scott
<x xml:space="preserve">Abstract</x> Background— Individuals with diabetes mellitus and pre–diabetes mellitus are at particularly high risk of incident heart failure or death, even after accounting for known confounders. Nevertheless, the extent of impairments in cardiac structure and function in elderly individuals with diabetes mellitus and pre–diabetes mellitus is not well known. We aimed to assess the relationship between echocardiographic measures of cardiac structure and function and dysglycemia. Methods and Results— We assessed measures of cardiac structure and function in 4419 participants without prevalent coronary heart disease or heart failure who attended the Atherosclerosis Risk In the Community (ARIC) visit 5 examination (2011–2013) and underwent transthoracic echocardiography (age, 75±6 years; 61% women, 23% black). Subjects were grouped across the dysglycemia spectrum as normal (39%), pre–diabetes mellitus (31%), or diabetes mellitus (30%) based on medical history, antidiabetic medication use, and glycated hemoglobin levels. Glycemic status was related to measures of cardiac structure and function. Worsening dysglycemia was associated with increased left ventricular mass, worse diastolic function, and subtle reduction in left ventricular systolic function (P⩽0.01 for all). For every 1% higher glycated hemoglobin, left ventricular mass was higher by 3.0 g (95% confidence interval, 1.5–4.6 g), E/E′ by 0.5 (95% confidence interval, 0.4–0.7), and global longitudinal strain by 0.3% (95% confidence interval, 0.2–0.4) in multivariable analyses. Conclusions— In a large contemporary biracial cohort of elderly subjects without prevalent cardiovascular disease or heart failure, dysglycemia was associated with subtle and subclinical alterations of cardiac structure, and left ventricular systolic and diastolic function. It remains unclear whether these are sufficient to explain the heightened risk of heart failure in individuals with diabetes mellitus.